The Role of Dynamic Knee Valgus in Occurrence of Knee Injuries: A Review Study - Ali Asghar Norasteh; Milad Fadaei Dehcheshmeh; Amir Shamlou Kazemi (Ṭibb-i Tavānbakhshī, 2023)
Background and Aims Dynamic knee valgus, as a poor movement pattern, may increase the risk of injury in the knee joint. This condition, which is related to a deviation in the lower limb alignment, can cause serious damage to the knee joint during tasks such as jump-landing, especially when bearing weight. The present study aims to investigate the role of dynamic knee valgus (DKV) in occurrence of knee injuries.Methods This is a review study. A search was conducted for the related articles published in English or Persian using the keywords Dynamic Knee Alignment, Dynamic Knee Valgus, Knee Joint Kinematics, Medial Collapse, Medial Knee Displacement, Frontal Plane Knee Excursion, Projection Angle, Dynamic Lower Extremity Valgus and Knee Injury in Science Direct, Scopus, PEDro, Google Scholar, PubMed, SID, ISC, Medlib, MagIran and IranDoc databases published from 2005 to May 2021. Initial search yielded 230 articles. After examining their full texts, 67 related articles were remained. Finally, 34 articles in the field of the role of DKV in occurrence of common knee injuries were selected for the review. Results Most of the studies were conducted on women and young people (aged 16-25 years). The DKV cause knee injuries such as anterior cruciate ligament injury (21 studies), patellofemoral pain syndrome (7 studies), tibiofemoral osteoarthritis (4 studies) and patellofemoral osteoarthritis (one study) as well as other cases such as osteoarthritis of the inner knee, chronic pain injuries in the hip and knee joints, and cartilage injuries. Conclusion DKV, as a poor movement pattern, put a person at risk of lower limb injuries. Muscle imbalance, muscle weakness, and impairment in the static alignment and its effect on dynamic alignment are among the most important mechanisms of DKV. Due to the structural and biomechanical characteristics, the most injuries caused by DKV occur in women.